NT-proBNP changes predict outcomes in elderly type 2 myocardial infarction patients - Jinling Ma; Ang Li; Suyan Bian (BMC Geriatrics)
Abstract Background N-terminal pro-B-type natriuretic peptide (NT-proBNP) is useful to predict adverse outcomes. Change in NT-proBNP level may provide additional actionable risk assessment information. This study aimed to determine the association of change in NT-proBNP level with adverse outcomes among elderly individuals with type 2 myocardial infarction (MI). Methods A retrospective analysis was conducted among elderly individuals with type 2 MI between December 2010 and December 2022. Change of NT-proBNP level was determined as the difference between the baseline and last measurement obtained during the period of 30 days. Results A total of 3007 participants aged 80 years and older were included. The patients were divided in accordance with the change in NT-proBNP level into those with NT-proBNP change ≥ 30% decrease, NT-proBNP change < 30% decrease and ≤ 10% increase, and NT-proBNP change > 10% increase. The patients with NT-proBNP change > 10% increase were older, had higher systolic blood pressure, loop diuretics use, and higher incidence of atrial fibrillation and chronic kidney disease. The quartile of change in NT-proBNP > 10% increase was markedly associated with increased risk of incident HF, as well as all-cause and cardiovascular mortality. The incidence rate of mortality increased in a graded fashion with change in NT-proBNP level. The Kaplan–Meier event-free curves showed that patients with NT-proBNP change > 10% increase had the highest risk, followed by those with NT-proBNP change < 30% decrease and ≤ 10% increase, and NT-proBNP change ≥ 30% decrease. Conclusions The change in NT-proBNP level can be used for identifying patients at a high risk of incident HF, as well as cardiovascular and all-cause mortality in elderly individuals with type 2 MI. It may be a promising biomarker to guide personalized therapy optimization.